Pengaruh Corporate Governance dan Leverage Pada Agency Cost - Sadewa, Nanda; Yasa, Gerianta Wirawan (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 11 No 1 (2016)DO - 10.24843/JIAB.2016.v11.i01.p03, 2016)
The purpose of this research is to know the influence of corporate governance and leverage on agency cost. This research is done within the scope of the firms that listed in Indonesia Stock Exchange. Observation is done in all sectors of the firms in 2009-2013. Samples are defined by using purposive sampling method thus 92 samples are obtained that match with criteria. This research uses multivariate regression as analysis technique. The hypothesis of this research said that corporate governance and leverage have a negative influence on agency cost. The result shows that corporate governance and leverage have positive and significant influence on agency cost. This research prove that the increasing of corporate governance and leverage in a firm, agency cost also increased. Keywords: Agency cost, corporate governance, leverage
Keywords: agency cost, corporate governance, leverage